The Significant of parents’ income toward students’ ability in learning Englis of pre-Internasional students at Economic and Business Faculty of Malikussaleh University - Hanif; Henny Irawati; Rosdiana (Almufi Journal of Measurement, Assessment, and Evaluation Education, 2022)
This research was done to know the study of parents’ income toward students’ ability in learning English. The purpose of this research is to find out the influance of parents’ income toward students’ ability in learning English. Family’s income is one of the students’ backgrounds that effect the students’ success in learning English at college. The test and questionares were used as an intrument to collect the data and information. The population of this study was the students at pre-internasional at accounting programe of Economic faculty of Malikussaleh university was taken as the sample for this study. The data collected was analyzed by using the statiscal procedures. The anova analysis was used to test the hyothesis that the students who are coming from better economic family income will have higher capabilty in the English than those who come from lower economic family income. This finding revealed that the students from lower family income have the equal ability in learning English with the students from middle or higher family income one.